Husband’s Support, Work Environment, and Exclusive Breastfeeding in Health Department of Bengkulu Province - Sanisahhuri Sanisahhuri; Sri Wahyuni; Susilo Wulan (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
Every baby has the right to get exclusive mother's water from birth for 6 (six) months, except for medical indications. During the provision of breast milk, the family, the government, the local government and the community must fully support the mother's baby with the provision of special time and facilities. Provision of special facilities is held at work and in public places. The purpose of this study was to determine the factors related to the provision of exclusive breastfeeding by mothers who worked in the Bengkulu Provincial Health Office. The study was conducted using Cross Sectional research design. The population in this study is all mothers who have children under the age of five years using total sampling technique. Data collection techniques using primary data by distributing questionnaires and secondary data are data obtained from the study of documents or files in the Bengkulu Provincial Health Office. Data were analyzed by univariate and bivariate using Chi-Square statistical test. The results of this study indicate that there is a significant relationship between the knowledge of mothers with exclusive breastfeeding by working mothers in the Bengkulu Provincial Health Office, namely 63.6% of mothers who have sufficient knowledge not to provide exclusive breastfeeding, then there is no significant relationship between husband's support and work environment with Exclusive breastfeeding by working mothers at the Bengkulu Provincial Health Office. Keywords: exclusive breastfeeding, husband’s support, mother knowledge, work environment